Genetic instability in Drosophila melanogaster mediated by hobo transposable elements. - Sheen, F.M.; Lim, J.K.; Simmons, M.J. (Genetics, 1993)
Eight independent recessive lethal mutations that occurred on derivatives of an unstable X chromosome (Uc) in Drosophila melanogaster were analyzed by a combination of genetic and molecular techniques. Seven of the mutations were localized to complementation groups in polytene chromosome bands 6E; 7A. In situ hybridization and genomic Southern analysis established that hobo transposable elements were associated with all seven of the mutations. Six mutations involved deletions of DNA, some of which were large enough to be seen cytologically, and in each case, a hobo element was inserted at the junction of the deletion's breakpoints. A seventh mutation was associated with a small inversion between 6F and 7A-B and a hobo element was inserted at one of its breakpoints. One of the mutant chromosomes had an active hobo-mediated instability, manifested by the recurrent production of mutations of the carmine (cm) locus in bands 6E5-6. This instability persisted for many generations in several sublines of an inbred stock. Two levels of instability, high and basal, were distinguished. Sublines with high instability had two hobo elements in the 6E-F region and produced cm mutations by deleting the segment between the two hobos; a single hobo element remained at the junction of the deletion breakpoints. Sublines with low instability had only one hobo element in the 6E-F region, but they also produced deletion mutations of cm. Both types of sublines also acquired hobo-mediated inversions on the X chromosome. Collectively, these results suggest that interactions between hobo elements are responsible for the instability of Uc. It is proposed that interactions between widely separated elements produce gross rearrangements that restructure the chromosome and that interactions between nearby elements cause regional instabilities manifested by the recurrence of specific mutations. These regional instabilities may arise when a copy of hobo transposes a short distance, creating a pair of hobos that can interact to produce small rearrangements.